(untitled) (International Nexus Multidisciplinary Research Journal, 2025)
The study investigated academic motivation and locus of control as predictors of academic performance among public secondary school students in Anambra State. The study was guided by three research questions and three null hypotheses tested at 0.05 level of significance. The study adopted correlational research design. The population of the study comprised 13742 senior secondary two (SS2) students. A sample of 389 respondents was drawn using Taro Yamane. Proportionate stratified random sampling technique was used to draw the sample. Two instruments used for data collection were; Academic Motivation Scale (AMS) and Locus of Control Scale (LCS). The instruments were validated by three experts from the department of Educational Foundations, Chukwuemeka Odumegwu Ojukwu University. The reliability of the instrument was established using Cronbach Alpha. The computation yielded Co-efficient values of 0.74 for AMS and 0.82 for LCS. Simple linear and multiple regressions were used for data analysis. The findings of the study revealed that academic motivation has a moderate predictive value for English language and a modest predictive value for mathematics and for academic performance. The findings also showed that locus of control had a weak positive predictive value for academic performance in English language and Mathematics. The findings suggest that the joint predictive value of the academic motivation and locus of control for academic performance in English and Mathematics was moderate and weak respectively. Based on the findings, teachers should incorporate motivational strategies into their teaching methods to stimulate student’s interest in subjects like English language and Mathematics.